The Convention of Saint Germain-en-Laye dated September 10, 1919 on the Abolition of Slavery in Africa and its Ratification by Türkiye in the Treaty of Lausanne - Gürsoy Şahin (Yakın Dönem Türkiye Araştırmaları)
The study purposes to examine the content of the Convention of Saint Germain-en-Laye dated September 10, 1919 about Africa and slave trade, which Türkiye committed to participate and ratify as required by the Treaty of Lausanne. This contract underlined in the Lausanne Treaty is generally mentioned in the sources with the principles for preventing the slave trade. However, the convention declared that the states exercising their sovereign rights in the African territories would continue to oversee the protection of the indigenous population and inspect the improvement of their material and spiritual welfare. Again, according to the agreement, efforts would also be made to ensure the abolition of all types of slavery in particular, as well as slave trade by sea and land. Moreover, decisions were made regarding issues such as the future of Africa, water basins, commercial equality, and etc. In this way, through the Treaty of Lausanne, Türkiye was involved in the issues related to Africa and slavery, as well as became a party to the decisions taken on this issue in the international field. The basic sources of the study involve official publications, Ottoman Archive documents, and the Minutes of the Grand National Assembly of Türkiye.